Analytical, Biological, Pharmacokinetic And Stability Studies Of Piper Sarmentosum Roxb. Extracts And Selected Studies Of Orthosiphon Stamineus Benth.Extracts - Hussain, Khalid (2009)
The study aimed to perform analytical and biological activity studies on root, stem, leaf and fruit of Piper sarmentosum and leaves of Orthosiphom stamineus, pharmacokinetic and stability studies on ethanol extract of fruit of Piper sarmentosum. Tujuan kajian adalah untuk menjalankan kajian analisis dan biologi ke atas akar, batang, daun dan buah Piper sarmentosum dan daun Orthosiphon stamineus, farmakokinetik dan kajian kestabilan ke atas ekstrak etanol buah Piper sarmentosum.